Diets supplemented with microalgal biomass: effects on growth, survival and colouration of ornamental fish Hyphessobrycon eques (Steindacher 1882) - Berchielli-Morais, Flavia Almeida [UNESP]; Kochenborger Fernandes, Joao Batista [UNESP]; Sipauba-Tavares, Lucia Helena [UNESP] (Wiley-Blackwell, 2016)
This study evaluated the effects of the addition of microalgae (Ankistrodesmus gracilis and Haematococcus pluvialis) to the fish diet in improving the growth and optimal pigmentation (red carotenoid) of Hyphessobrycon eques. The basal mixed diets consisted of a formulated diet, supplemented with dried microalgae biomass of A. gracilis (1.5 g kg(-1)) and H. pluvialis (1.5 g kg(-1)). The live food diets contained zooplankton was cultured in open ponds, associated with microalgae. All the microalgae were cultured in the laboratory. No mortality was observed with any experimental diets. Fish performance results showed significant differences (P < 0.05) between the basal diet (BD) and the live food diet. The higher weight and total length were observed with mixed diets (BD + H. pluvialis and BD + A. gracilis). The mixed diets promoted more intense values of chroma (Cab*), lightness (L*) and redness (a*) to H. eques. Diaphanosoma birgei (Cladocera) represented more than 32% of zooplankton ingested by ornamental fish in live food (zooplankton and zooplankton + microalgae), and Argyrodiaptomus furcatus (Copepoda) was the species most ingested by H. eques in live food dietary treatment zooplankton. The feeding behaviour observed in the laboratory as well as the food preferences of H. eques was dependent on the zooplankton composition present in the used open ponds. This study showed that diets with microalgae and zooplankton were able to enhance the pigmentation of H. eques, being a good tool to benefit the culture management of this species.
Keywords: zooplankton; feeding activity; Ankistrodesmus gracilis; Haematococcus pluvialis; basal diet